1981
DOI: 10.1128/iai.32.1.353-363.1981
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Modification, Rosette-Forming Cells, and Salmonella typhimurium Resistance in Outbred and Inbred Mice

Abstract: To assess the separate contributions of host T cells and the physical state of the antigen in the development of effective Salmonella resistance, glutaraldehyde-treated and untreated proteinand ribonucleic acid-rich extracts (E-RNA extracts) of virulent Salmonella typhimurium SR-li or attenuated S. typhimurium RIA were used to immunize Salmonella-resistant and Salmonella-susceptible strains of mice for the purpose of determining whether antigen-specific Tcell or B-cell responses were formed and, if so, which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
1983
1983

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In a recent study we demonstrated that the splenic lymphocytes of S. typhimurium-immune mice will form antigen-specific rosettes with coated SRBC (3). The majority of these RFL were found to be sensitive to antithymocyte serum plus complement.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In a recent study we demonstrated that the splenic lymphocytes of S. typhimurium-immune mice will form antigen-specific rosettes with coated SRBC (3). The majority of these RFL were found to be sensitive to antithymocyte serum plus complement.…”
Section: Resultsmentioning
confidence: 97%
“…Antigen-specific rosette formation assay. The procedure used to detect Salmonella-specific RFL was essentially that of Bigley et al (3). Briefly, to a 10-by 75-mm culture tube was added 0.1 ml of splenic lymphocytes (108/ml) and 0.2 ml of a 1% suspension of antigen-coated (Salmonella or Listeria) or normal SRBC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C3H/HeJ strain of mice is resistant to the lethal and adjuvant effects of endotoxin (6,22). Although these mice are very susceptible to the lethal effects of a challenge infection with S. typhimurium (LD50 < 10 bacteria), they can be protected from a lethal challenge infection after vaccination with the avirulent RIA strain of S. typhimurium (1). Both host protection to challenge infection and footpad swelling responses (DH) were demonstrated in these mice after receipt of TF prepared from the spleens of immune ICR Swiss mice.…”
Section: Discussionmentioning
confidence: 99%